Changes in Locomotor Fundamental Movement Skills Scores Following Hadang-Based Learning: A One-Group Pretest–Posttest Study among Fourth-Grade Primary School Students - Lanos, Muhsana El Cintami; Hawaini, Hawaini; Junaidi, Ilham Arvan (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2026)
Locomotor fundamental movement skills, including running, galloping, hopping, leaping, horizontal jumping, and sliding, provide an essential foundation for children's movement competence and participation in physical education. Traditional games, such as Hadang, offer meaningful and enjoyable opportunities for children to repeatedly practice these locomotor skills in authentic movement contexts. This study examined changes in locomotor fundamental movement skill scores before and after eight sessions of Hadang-based learning among fourth-grade primary school students. A pre-experimental study employing a one-group pretest–posttest design was conducted with 30 fourth-grade students from Primary School 1 Peninggalan. Locomotor performance was assessed using the Test of Gross Motor Development–Second Edition (TGMD-2) locomotor subtest, which evaluates six locomotor skills: run, gallop, hop, leap, horizontal jump, and slide. Following the learning period, the mean locomotor raw score increased from 10.10 (SD = 1.82) at pretest to 16.27 (SD = 2.05) at posttest. A paired-samples t-test indicated a statistically significant difference between pretest and posttest scores (t(29) = −22.614, p < 0.001). The findings indicate that participants achieved higher locomotor fundamental movement skill scores at posttest than at pretest over the study period. However, because the study employed a one-group pretest–posttest design without a comparison group, the observed within-group changes cannot be attributed solely to Hadang-based learning and should be interpreted cautiously. Future studies using controlled experimental designs are recommended to strengthen the evidence regarding changes in children's locomotor fundamental movement skills.